PENCIPTAAN KARYA TEATER BAYANG RAGA NUSANTARA DOOMED ROMANCE - Gunawan, Gede Putra Arya Bagus; Marajaya, I Made; Sudarta, I Gusti Putu (JURNAL DAMAR PEDALANGAN, 2025)
The performance Shadow Theater: Raga Nusantara adapts traditional Balinese wayang techniques, blending them into a modern theater performance that tells the love story of Sri Tanjung and Sidapaksa, a tale believed by the Banyuwangi community. The Raga Nusantara shadow theater applies methods from Eko Supriyanto’s book “Ikat Kait Impulsif Sarira”—namely Re-Visiting, Re-Questioning, and Re-Interpreting. This work, titled Doomed Romance, translates to a shattered romance or broken love. The shadow theater piece, Doomed Romance, originates from the social phenomena prevalent among the younger generation, particularly concerning the dynamics of romantic relationships. This phenomenon reflects various aspects of young people's lives as they undergo the process of searching for identity, self-existence, and the meaning of love in an ever-changing social context. Romantic relationships often become an important part of their lives, involving not only emotions but also complex social interactions. This work narrates the love journey of Sri Tanjung and Sidapaksa, filled with obstacles and temptations, which form the dynamics of their romantic story. The story carries many moral messages and meanings, particularly in the realms of romance and trust. This tale is considered relevant to the phenomena experienced by the younger generation undergoing the dynamics of social or romantic relationships, which is why the artist chose this story for the Raga Nusantara shadow theater.